ChemInform Abstract: Minor Withanolides of Physalis longifolia: Structure and Cytotoxicity. Issue 12 (14th March 2013) - Zhang, Huaping; Motiwala, Hashim; Samadi, Abbas; Day, Victor; Aube, Jeffrey; Cohen, Mark; Kindscher, Kelly; Gollapudi, Rao; Timmermann, Barbara
Abstract Two new minor withanolides, i.e.